Respuesta :
Answer:
Explanation to the answer below... (Answers in the Explanation)
Step-by-step explanation:
We Know that our rule is y = [tex]y = -6(3)^{x}[/tex] , which means we can use this rule to find y from x. Since we don't know what X, is, we have to assume numbers like 1, to 7. And there is no space to write on the graph, I'll put a virtual copy of a graph.
1st Point,
[tex]y = -6(3)^{x}\\y = -6(3)^{1}\\y = -6(3)\\y = -18\\x = 1, y = -18[/tex]
2nd, point
[tex]y = -6(3)^x\\ y = -6(3)^2\\y = -6(9)\\y = -54\\x = 2, y = -54[/tex]
3rd Point
[tex]y = -6(3)^x\\y = -6(3)^3\\y = -6(27)\\y = -162\\x = 3, y = -162[/tex]
4th Point
[tex]y = -6(3)^4\\y = -6(81)\\y = -486\\x = 4, y = -486\\[/tex]
5th Point
[tex]y = -6(3)^5\\y = -6(243)\\y = -1458\\\x = 5, y = -1458[/tex]
6th Point
[tex]y = -6(3)^x\\y = -6(3)^6\\y = -6(729)\\y = -4,374\\x = 6, y = -4,374\\[/tex]
7th Point (Last Point)
[tex]y = -6(3)^x\\y = -6(3)^7\\y = -6(2,187)\\y. = -13,122\\x = 7, y = -13,122[/tex]
Let's now plot them on the Graph, the values are so big, the graph might look a little odd.
Always remember that we can continue the points infinitely, and there is no stop, The Graph is attached below...